Development and Validation of Digital Readiness Assessment Instrument for Rural Enterprises: Evidence from BUMDES in Indonesia - Abdurokhim Abdurokhim; Dendi Pratama; S. Sulastri; Whan Augustin Ainul Amri; Askarno Askarno (Daengku: Journal of Humanities and Social Sciences Innovation, 2026)
Digital transformation remains a critical challenge for rural enterprises in developing economies, yet validated instruments to assess digital readiness in this context are scarce. This study develops and validates a comprehensive Digital Readiness Assessment (DRA) instrument specifically tailored for Badan Usaha Milik Desa (BUMDES) – Indonesia's village-owned enterprises. Through mixed-method research involving literature review, expert consultation, and empirical testing with 100 BUMDES in Cirebon Regency, we developed a 60-item instrument measuring five dimensions: awareness, management support, infrastructure, skills, and budget allocation. The instrument demonstrated excellent reliability (Cronbach's ? = 0.924) and strong construct validity through confirmatory factor analysis. Results reveal a significant paradox: while 67.4% of BUMDES show high awareness of digital importance, only 34.2% possess adequate digital skills and 31.8% allocate sufficient budget. ANOVA analysis (F=84.73, p<0.001) confirms significant differences across readiness dimensions, with awareness-capability gap identified as the primary barrier. Cluster analysis identifies three distinct readiness profiles: 'High Awareness-Low Capability' (43%), 'Moderate Readiness' (49%), and 'Digital Ready' (8%). The validated DRA instrument provides researchers and practitioners with a robust tool for assessing and benchmarking digital readiness in rural enterprise contexts, while findings inform targeted intervention strategies for digital transformation support.